Enhanced bioremediation of saline azo dye effluents using PersiLac3: A thermo-halotolerant laccase from a tannery metagenome - Shohreh Ariaeenejad; Kaveh Kavousi; Mehrshad Zeinalabedini; Donya Afshar Jahanshahi; Seyed Reza Beh-Afarin (Results in Engineering)
Large quantities of recalcitrant azo dye wastewater represent an important environmental issue, owing to their toxicity and the difficulty of their treatment under hypersaline conditions. By maintaining high activity under salt-rich conditions, salt-tolerant laccases offer a promising solution for the effective breakdown of toxic azo dyes, making them indispensable for the sustainable treatment of industrial wastewater. This study explored the identification and application of a thermo-halotolerant laccase, PersiLac3, for bioremediation of azo dye wastewater under high-salt conditions typical of textile effluents. The broad substrate oxidation potential of PersiLac3 was assessed across diverse temperatures, pH levels, and challenging conditions, such as high salt levels, and in the presence of organic solvents and inhibitors. Remarkably, PersiLac3 showed enhanced activity (112.25 %) in 3 M NaCl, highlighting its superior ability to adapt to saline conditions. Kinetic studies of PersiLac3 indicated high efficiency and affinity for its substrate at saline concentrations ranging from 1 to 6 M NaCl. PersiLac3 effectively decolorized the Congo red dye (82.9 %) in highly concentrated solutions (5000 mg/L) within 15 min, and its performance was further improved in the presence of wastewater-relevant ions, achieving 92.3 % dye removal. Monitoring real wastewater treatments, PersiLac3 reduced optical density, underscoring its potential for application in the bioremediation of dye-laden and saline wastewater streams. The adaptability of PersiLac3 to harsh, high-salinity environments, coupled with its rapid dye decolorization efficiency, is an innovative and powerful tool for addressing environmental pollution challenges and advancing waste treatment methodologies.